The National Health Service - Great Britain. Central Office of Information. (London : His Majesty's Stationery Office, 1948)
1948 1948 1940s 38 pages reduce the number of doctors by not filling practices when they fall vacant, so long as other areas suffer from a shortage. The young doctor just starting in practice and the established doctor moving to a new district are free to come into the Service anywhere in the country except in the few areas on the 'full-up' list ; though they can, of course, practise in those areas if they remain outside the Service. This control is exercised not by the Ministry, but by a national Medical Practices Committee composed almost wholly of practising doctors.* The Executive Councils tell this committee the number of doctors required to meet the reasonable needs of their areas, and also report any vacancies occurring in the Service. The committee may refuse a doctor's application to join the Service in a certain area only 'on the ground that the number of medical practitioners undertaking to provide general medical services in the area or part of an area concerned is already adequate'. The Medical Practices Committee has the permanent duty of filling all vacancies occurring in the Service, since such vacancies will no longer be filled by purchase. When a departing doctor has to be replaced, the Executive Council will normally advertise the vacancy. If only one doctor applies he will usually be given the practice automatically. If several apply, the Executive Council, when reporting their names to the committee, will add the opinion of the Local Medical Committee and its own recommendations. Local ties and wishes, as well as local needs, will be taken into account. For instance, a partnership of doctors may want a particular man to join them, or a son may wish to carry on his father's practice. The doctor who has not been granted what he wanted may ask the Minister to overrule the committee or to appoint him in addition to the doctor chosen by the committee. The Dental Service The general dental service is managed in much the same way as the family doctor service. It is open to anyone who wants to use it (medical cards are not needed) ; people may go to any dentist in the Service, and change dentists when they wish. Mothers and children may use the service, too, but because of the shortage of dentists the local authority 'priority' service is designed and reserved for their special benefit. They may get much prompter attention if they use it instead of going to dentists in the general dental service. Both services will give the patient, free of charge, every form of treatment and appliance necessary for * It has nine members appointed by the Minister. Seven of them (including the chairman) are doctors appointed after consultation with doctors' organisations, of whom at least five must be 'actively engaged in medical practice'. 29 21/1489